2021
DOI: 10.3390/coatings11060629
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Powder Preparation for Additive Manufacturing Using Electrostatic Classification

Abstract: This work aims to study the possibility of using an electrostatic drum-type separator to prepare a powder with a narrow size distribution curve for usage in additive manufacturing. The size distributions of the uncoated commercial aluminum powders ASP-30, ASP-22, and ASP-5 were analyzed. It was shown that the powders ASP-30 and ASP-22 have similar asymmetric distributions with a SPAN of 1.480 and 1.756, respectively. ASP-5 powder, in turn, has a narrow distribution with a SPAN of 0.869. ASP-30 powder was chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In various works devoted to LPBF technology, it has been shown that the well-chosen initial powder material is the basis for the successful consolidation with minimum defects [ 31 , 32 , 33 , 34 , 35 ]. The most important properties of the powder are particle morphology, chemical composition, and microstructure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In various works devoted to LPBF technology, it has been shown that the well-chosen initial powder material is the basis for the successful consolidation with minimum defects [ 31 , 32 , 33 , 34 , 35 ]. The most important properties of the powder are particle morphology, chemical composition, and microstructure [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was confirmed that the organic coating of particles could be affected by various factors, such as particle size, pore size, pore area, and the amount of organic material used for coating. These factors should be adjusted and optimized depending on the characteristics of the particles [ 23 , 26 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metal powders are used in a wide range of industrial applications including 3D printing technologies [ 1 ], additive technologies [ 2 ], pyrotechnics [ 3 ], and ceramics production [ 4 ]. Increasing the reactivity of metal powders in various processes contributes to lower energy costs and saving resources [ 5 ].…”
Section: Introductionmentioning
confidence: 99%